The Scottish perinatal mortality survey. Issue 6198 (3rd November 1979) - McIlwaine, G M; Howat, R C; Dunn, F; Macnaughton, M C
Abstract : Perinatal deaths in single births that occurred in Scotland during 1977 were investigated by case-record analysis. Causes of death were divided into nine categories, an extended version of the Aberdeen classification being used. Out of 1012 single perinatal deaths, 265 were due to fetal abnormality, which in 140 cases was malformation of the central nervous system. Of the 747 normally formed infants, 446 weighed 1500 g or more, of whom 82 died intra partum and 154 were born alive. The largest single cause of death was low birth weight in normally formed babies whose mothers had no complications of pregnancy (302 cases). Of these babies, 103 (34%) were growth-retarded. Rhesus incompatibility (16 deaths) and maternal diabetes (seven deaths) were not major causes of perinatal loss. These results were thought to be valuable in illustrating the main causes of perinatal mortality and directing attention to important issues. Hence a modified version of the study is being continued to see whether yearly audit by regional assessors is a feasible and practical way of monitoring trends in perinatal mortality.